Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan dengan Ukuran perusahaan sebagai Variabel Intervening: Studi kasus perusahaan index LQ45 yang terdaftar di Bursa Efek Indonesia periode 2018-2022 - Alhoi Andrew Jefferson; Darwin Lie; Hendry; Merry Rusida (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
One of the most actively traded and liquid stock groups in the capital market is the LQ45 index, which consistently attracts investor attention due to its strong market capitalization and transaction volume. This study aims to analyze the influence of financial performance and financial management strategies on firm value among companies listed in the LQ45 index on the Indonesia Stock Exchange during the 2018–2022 period. The study population consisted of 73 LQ45-indexed companies, with purposive sampling used to select 23 companies that met the research criteria. This research employed a quantitative approach using path analysis to examine both direct and indirect relationships among variables. The findings indicate that profitability and leverage have a positive and significant effect on firm value. In addition, profitability and leverage also positively influence firm size, indicating that companies with stronger profitability and effective debt management tend to expand their operational scale. However, firm size does not significantly affect firm value and is unable to mediate the relationship between profitability, leverage, and firm value. These results suggest that investors place greater emphasis on profitability and leverage indicators than company size when evaluating firm value in LQ45 companies. Therefore, effective financial performance remains the primary factor in enhancing corporate value and investor confidence.